Pengaruh pemberian ekstrak bekatul beras hitam (Oryza sativa L. indica) terhadap kadar MDA, SOD dan trigliserida pada tikus diabetes mellitus tipe 2 - Monikasari Monikasari; Nyoman Suci Widyastiti; Endang Mahati; Ahmad Syauqy; Ahmad Ni’Matullah Al-Baarri (AcTion: Aceh Nutrition Journal, 2023)
In type 2 diabetes mellitus, the pancreas can produce the hormone insulin, but the body has difficulty using it. The study aimed to prove the effect of black rice bran extract on MDA, SOD, and triglyceride in type 2 Diabetic Mellitus rats. The method is quasi-experimental with a pre-posttest randomized control group design in 2021. The intervention was given for 21 days to 42 male Wistar rats. MDA examination using the TBARs method, SOD examination using a UV-Visible spectrophotometer. Triglyceride examination using a spectrophotometer. Statistical analysis used Paired T-Test or Wilcoxon test and One-Way ANOVA or Kruskal Wallis test. Descriptive research findings show that the intervention of black rice bran extract at a dose of 60 mg/200g reduced MDA in rats to 2,21 mmol/ml and triglycerides to 85,17 mg/dL. In addition, it can increase SOD to 69,67 units/ml. Almost the same as the intervention of metformin 9 mg/200 g body weight. However, statistically, no significant difference exists in the interventions carried out (p> 0,05). The study concluded a decrease in MDA, SOD, and triglyceride in rats, given the black rice bran extract intervention.